Exploring key parameters influencing student performance in a blended learning environment using learning analytics - S J, Shabnam Ara; R, Tanuja (Journal of Education and e-Learning Research, 2024)
Understanding the factors that influence students’ results in hybrid learning environments is becoming increasingly important in today’s educational environment. The goal of this research is to examine factors that influence students’ academic performance as well as their level of participation in blended learning environments. A comprehensive study was conducted with 330 interested participants from the prestigious government polytechnics of the state of Karnataka in order to achieve this goal. Our data acquisition approach relied on the administration of a meticulously crafted survey questionnaire. The conceptual framework underpinning this study seamlessly integrates Transactional Distance Theory (TDT) principles with valuable insights derived from prior research. The Welch test and one-way ANOVA (Analysis of Variance) are two statistical approaches that we used selectively to reinforce our research which produced surprising results. These findings underscore the pivotal role played by certain specific factors. The geographical location of learners and the medium through which they pursue their studies have emerged as critical determinants significantly influencing academic performance. Aspects like the frequency of login activities and active engagement in forum discussions have been found to exert a positive influence on learners’ academic performance. In contrast, the duration of sleep did not show a significant impact on performance. These insights bear tangible implications for teachers and policymakers who are dedicated to the enhancement of the quality of BL programs with the ultimate goal of enriching the overall educational experience.